Schiff Base Complexes: Synthesis, Characterization and Study of Bioactive Such As Antibacterial and Antifungal - kalaf gabar, Kaleda (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The complexes of Schiff base (6-[Hydroxy - benzylidene)-amino]-pyrimidine-2,4-diol ) (L) with Mn(II), Fe(II), Co(II) and Ni(II) were prepared. The Schiff base and complexes have been characterized by FT-IR, 1H-NMR, UV-Vis, LC-mass spectra, magnetic moment, elemental microanalyses (C.H.N.), chloride containing, atomic absorption and molar conductance. The Schiff base, metal salts and complexes were also screened for their bioactivity such as antibacterial and antifungal.